Growth Performances and Productivities of Kappaphycus alvarezii and Eucheuma spinosum Cultivated with Long-line Method in PT. Sea Six Energy Indonesia - Chairun Nisa, Andina; Jatayu, Diklawati; Alfiani, Putu Putri (Department of Aquaculture, 2024)
Indonesia is the second largest producer of seaweed in the world. Different cultivated seaweed commodities may have different production results. This study aimed to determine the effect of cultivation time and different types of seaweed on total weight and Specific Growth Rate (SGR) of Kappaphycus alvarezii and Eucheuma spinosum cultivated with the long-line method. The study was conducted in one cultivation area, PT. Sea Six Energy, Bali, Indonesia. Data collection was carried out through observations in 2 sites. Every site contained 3 square frame seaweed Kappaphycus alvarezii and Eucheuma spinosum. The sample used in this study was one thallus of seaweed taken randomly from 3 different ris ropes in each square frame. The average weight of thallus, total weight, and specific growth rate were performed in this study. After 51 days, the total weight of K. alvarezii was 1348.5 kg. The total weight of E. spinosum was 1398.7 kg. Both, K. alvarezii (8.4 ± 0.34 %.day-1) and E. spinosum (8.3 ± 0.02 %.day-1) showed higher Spesific Growth Rate (SGR) in the first 2 weeks of planting but not in the last 3 weeks of cultivation. There was no difference in productivity between K. alvarezii and E. spinosum cultivated using the long-line method. However, this research showed that the SGR value decreased as cultivation time increased.